2010
DOI: 10.4103/0971-5851.71656
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian tumors in pediatric age group - A clinicopathologic study of 10 years′ cases in West Bengal, India

Abstract: Background and objectives:Objective in this retrospective study is to find out the incidence of different ovarian tumors of girls up to 20 years of age observed in last ten years in North Bengal Medical College and to correlate clinical and gross findings with histopathologic findings and to compare the incidence with other studies and follow-up of patients with malignant ovarian tumors.Materials and Methods:Findings were retrieved from records of different pathological reports and clinical reports.Results:Tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 6 publications
1
21
2
3
Order By: Relevance
“…No documented emergent acute abdomen unlike some reports [10,11]. None of our 2 JSCT cases has precocious puberty, however Bhattacharyya et al [2] in India found 2 cases with precocious puberty out of 3 in his series of 151 malignant pediatric ovarian tumor patients.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…No documented emergent acute abdomen unlike some reports [10,11]. None of our 2 JSCT cases has precocious puberty, however Bhattacharyya et al [2] in India found 2 cases with precocious puberty out of 3 in his series of 151 malignant pediatric ovarian tumor patients.…”
Section: Discussioncontrasting
confidence: 47%
“…[1,2]. Tumors of the ovary may be benign like mature cystic teratomas or malignant like yolk sac tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian malignancy accounts for 1% of all the childhood tumours in the previous studies but some studies like Oumachigui et al, 1991 and Sawai MM et al, 1973 found the incidence to be as high as six per cent and 11.2% respectively [2, 11, 12]. In the study conducted by Bren JL et al it was reported that 35% of all ovarian neoplasms in childhood and adolescent were malignant (Bren JL et al, 1977) [13].…”
Section: Discussionmentioning
confidence: 99%
“…They account for 1% of all the childhood malignancies and 8% of all abdominal tumours in children. It is estimated that almost 10-30% of all the ovarian neoplasms occurring in girls up to 17 years of age are malignant [1, 2]. Tumours of the Ovary are divided into neoplastic and non-neoplastic processes.…”
Section: Introductionmentioning
confidence: 99%
“…There were 9 cases of malignant surface epithelial tumour. 7 In the prospective study conducted at the Department of Obstetrics and Gynaecology, Tribhuvan University, 80 cases in childhood and adolescent were studied, majority belonged to 15-19 years. Germ cell tumours account for 73.7%.…”
Section: Discussionmentioning
confidence: 99%